2015
DOI: 10.1111/jfpp.12500
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Changes Related to Loss of Quality in Pacific White Shrimp (Litopenaeus vannamei) during Chilled Storage under Slurry Ice Conditions

Abstract: The effect of slurry ice on the quality of Pacific white shrimp (Litopenaeus vannamei) during chilling storage was investigated and compared with flake ice. Increases of total volatile base nitrogen and thiobarbituric acid reactive substance values in shrimp treated with slurry ice were found to be significantly slower during slurry ice storage than its values during flake ice storage (P < 0.05). Slurry ice-treated samples showed significantly higher springiness and chewiness variables than control (stored at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…Due to high content of unsaturated fatty acids, lipid oxidation always happened during shrimp preservation. Previous reports showed that MDA concentration of flake‐iced shrimp reached 2.942 mg MDA kg −1 muscle at 8 days during chilled storage . As a major peroxidant of lipid oxidation, MDA contains two reactive carbonyl functional groups that react with free amino groups in proteins, especially the ϵ ‐amino of Lys, and with the nucleophilic side chains in Cys and His .…”
Section: Resultsmentioning
confidence: 99%
“…Due to high content of unsaturated fatty acids, lipid oxidation always happened during shrimp preservation. Previous reports showed that MDA concentration of flake‐iced shrimp reached 2.942 mg MDA kg −1 muscle at 8 days during chilled storage . As a major peroxidant of lipid oxidation, MDA contains two reactive carbonyl functional groups that react with free amino groups in proteins, especially the ϵ ‐amino of Lys, and with the nucleophilic side chains in Cys and His .…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al . (2015) investigated the changes in the TVB‐N value of L. vannamei stored under slurry ice conditions and revealed that the TVB‐N value of samples treated with slurry ice remained at 19.38 mg/100 g after 16 days of chilled storage (icing storage) . These results indicated that the TVB‐N value could be limited effectively by simply lowering the storage temperature.…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…Lipid peroxidation, corresponding to oxidative deterioration of polyunsaturated fatty acids in muscle, leads to the production of off flavors and off odors, thereby shortening the shelf life of seafood . Thiobarbituric acid reactive substances, the products of secondary lipid oxidation, have a close correlation with sensory assessment in aquatic products .…”
Section: Physicochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations